Taken Boys and Mistaken Benevolence in the Early Modern English Theatre and the Virginia Company - Bryan, Emily D. (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
This article analyzes overlooked evidence concerning the conscription of boys by early modern English choirs and theatre companies, arguing that legal and cultural representations depicted these abductions as benevolent while violating consent. It further speculates that points of contact between the theatrical economy and the Virginia Company may have prompted authorities to use a parallel mode of impressment to take Powhatan children to populate Henrico College. I argue that the practices of coercion and abduction on the English stage can provide a useful framework for understanding the rhetoric of benign subservience that the English authorities cultivated in an Atlantic context.